Drinking green tea: despite the risks due to mycotoxins, is it possible to increase the associated health benefits? - Assunção, Ricardo (2021)
Project “Resistant mycobiota and mycotoxigenic profile of tea and medicinal plants” (IPL/2020/TEAResMyc_ESTeSL).